Keterwakilan Perempuan Di Dewan Perwakilan Rakyat Pasca Putusan Mahkamah Konstitusi Nomor 22-24/PUU-VI/2008 - Kurniawan, Nalom (Mahkamah Konstitusi Republik Indonesia, 2014)
Affirmative action by giving 30% quota for women, is a constitutional rights that must be seen in proportional viewed without override the right of people sovereignty. As a major stakeholder in the democratic state, is the right of people to elect their representatives to sit in parliament. Waiver of the right of people to elect their representatives is a violation in the democracy system and a violation of people sovereignty.